PENINGKATAN KUALITAS PRODUK MEBEL MELALUI APLIKASI FINISHING BERNUANSA MARMER DAN GRANIT - Muchoyar, Imam; Ikhwanuddin, Ikhwanuddin (Universitas Negeri Yogyakarta, 2005)
The aim of the training Ipteks program is to upgrade of cracking painting finishing skill for carpeter so that they aschive product variations to enhances customer interest.The training is executed in Bantul District, trainers are 15 person. The training is execute one weeks continuously, with the instrucors from PT Propan Raya Yogyakarta and FT Yogyakarta State University. Activity method are impel of working and producing with material: (l) finishing teory, (2) demonstration, (3) apppiication of finishing marble and granite nuanced at training place, and (5) application of finishing on their shops.The result are: (1) The trainers mastery in theory and practice of finishing marble and granite, (2) There are able to material for on their own production, (3) tere able to apply for on their own production, and (4) so that they can make product variations that sell in their own show rooms.Key words: marble, granite.furniture, small-middle industry